Conciliação entre modelos de mecanismos avançados de oxidação eletroquímica - Oliveira, Gustavo Rodrigues de (2012)
Many pollutants dumped in waterways, such as dyes and pesticides, have become so ubiquitous that they represent a serious threat to human health. The electrochemical oxidation is presented as an alternative clean, efficient and economic degradation of wastewater containing organic compounds and a number of advantages of this technique is to just not make use of chemical reagents, since only electrical energy is consumed during the removal of pollutants organic. However, despite being a promising alternative, still needs some tweaking in order to obtain better efficiency in the elimination of persistent pollutants. Thus, this study sought a relationship between a recently discovered phenomenon that reflects the participation of dissolved oxygen in solution in the electrochemical oxidation process, as an anomaly, present a kinetic model that shows instantaneous current efficiency (ICE) above 100% limited by theory, manifested for some experiments with phenolic compounds with H2SO4 or HClO4 as supporting electrolyte with electrodes under anodic oxidation on boron doped diamond (BDD). Therefore it was necessary to reproduce the data ICE exposes the fault model, and thus the 2-naphthol was used as phenolic compound to be oxidised at concentrations of 9, 12 and 15 mmol L-1, and H2SO4 and HClO4 to 1 mol L-1 as a supporting electrolyte under a current density of 30 mA cm-2 in an electrochemical reactor for continuous flow disk configuration, and equipped with anodes DDB at room temperature (25 oC). Experiments were performed using N2 like as purge gas for eliminate oxygen dissolved in solution so that its influence in the system was studied. After exposure of the anomaly of the ICE model and investigation of its relationship with dissolved O2, the data could be treated, making it possible for confirmation. But not only that, the data obtained from eletranálise and spectroscopic analysis suggest the involvement of other strongly oxidizing species (O3 (ozone) and O radicals and O2 -), since the dissolved O2 can be consumed during the formation of new strong oxidizing species, not considered until now, something that needs to be investigated by more accurate methods that we may know a little more of this system. Currently the performance of the electrocatalytic process is established by a complex interaction between different parameters that can be optimized, so it is necessary to the implementation of theoretical models, which are the conceptual lens with which researchers see